MEKANISME PENERBITAN SAHAM SYARIAH PADA EMITEN SYARIAH - Antoni Antoni; Bachtiar Rahman Halik (Cross-border, 2022)
One of the products sold in the capital market is stock. Shares are securities issued by issuers as a means of linking long-term capital. Shareholders have the right to demand dividends provided by the company's articles of association. Issuance conducted by the Sharia Securities Board to screen stocks that meet the criteria of sharia principles. This research is qualitative with a descriptive approach by describing laws, DSN MUI and OJK fatwas to find out the regulations in the Sharia Securities List (DES). (DES) issued by OJK in stages.